Body and Resistance in Mahasweta Devi’s The Queen of Jhansi - Bimal Prasad Adhikari (Journal of Development Review, 2025)
This study examines how the struggle and ideological transformation in hegemonic Indian society are reflected in the bodily experiences of the underprivileged people during colonial era of Bengal during 1850s. The dominated peoples’ bodily transformation allows them to attain their autonomous selves via agency and bodily resistance. This study examines why and how Devi’s protagonist Lakshmibai undergoes bodily transformation, why Mahasweta Devi portrays such experiences in her novel The Queen of Jhansi (1956). By undergoing the body’s transformational rites, the character acquires the agency to oppose injustice. To examine bodily transformation as a site of resistance against colonial and societal oppression, the research incorporates theoretical insights of Victor Turner, Michael Garnett, and Antonio Gramsci to explore themes of liminality, agency and bodily transformation. Lakshmibai preserves her identity and dignity while establishing her own agency and solidarity following liminality, a political process that turns the self into agency in order to fight against social injustice. Communitas is a harmonious space where individual reclaims identity through liberty. Devi’s The Queen of Jhansi (1956) depicts the protagonist Lakshmibai’s massive physical repression and reintegration into a new community, as well as the rituals of bodily alteration as a site of resistance. Through the protagonist’s transformation from a state of powerlessness to an empowered quest for autonomy, the notion that subalterns cannot speak is dismantled.